The St. Petersburg Paradox despite risk-seeking preferences. An experimental study - Eike Benjamin Kroll; Bodo Vogt (Verein für Socialpolitik, 2010)
The St. Petersburg Paradox is one of the oldest violations of expected utility theory. Thus far, explanations of the paradox aim at small probabilities being perceived as zero and the boundedness of utility. This paper provides experimental results showing that neither risk attitudes nor perception of small probabilities explain the paradox. We find that even in situations where subjects are risk-seeking, the St. Petersburg Paradox exists. This indicates that the paradox lies at the very core of human decision-making processes and cannot be explained by the parameters discussed in previous research so far.
Keywords: C91; D81; D80; 330